(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
A shallowing-upward carbonate sequence was studied from the outcrop at Gyulakeszi, Tapolca Basin (western Hungary), and it is interpreted as a Middle Triassic (Curionii or younger) platform progradation. Two lithostratigraphic units are distinguished. Microfacies analysis and micropaleontological investigation conducted on the red nodular, cherty limestone (Vászoly and Buchenstein formations) suggest that the lower unit was deposited during the Reitzi and the Secedensis ammonoid zones. The overlying white platform limestone (upper unit) is typical of a prograding platform and includes gravity-driven deposits at the base followed by periplatform facies deposited in shallow marine warm waters around the fair-weather wave base. The section at Gyulakeszi was unaffected by fabric-destructive dolomitization, which is uncharacteristic of similar platform facies in the Balaton Highland. Isopachous and radiaxial fibrous calcite cement found in the grainstone and boundstone facies are indicative of early lithification and diagenesis in the marine phreatic zone. “Evinospongiae”-type cement is described for the first time from the Balaton Highland and it is similar to the outer platform cements published previously from the Alps (Italy and Austria). The progradation could have advanced over the pelagic limestones as early as the Curionii zone, which is an undocumented event in the Veszprém Plateau. Similar event, however, is well known from the Western Dolomites, where aggradation was followed by intense progradation during the Gredleri and Archelaus ammonoid zones. The length of this progradation event at Gyulakeszi, however, is ambiguous since proven Ladinian (Longobardian) rocks are not exposed in the study area and were not penetrated by boreholes in the Tapolca Basin.